One Visit Providing Desirable Smile by Laser Application - Fekrazad, Reza; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2013)
Introduction: Providing desirable smile is one of the main concerns in cosmetic dentistry. Hyperpigmentation is one of the esthetic concerns especially in gummy smile patients. Lasers with different wavelength are used for oral surgery including Carbon Dioxide Laser (CO2), Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG), Erbium family and diode laser. In this case, all esthetic procedures including gingival depigmentation, caries detection and removal were done by laser technology in one session. Case study: A 40- year-old male with a chief complaint of black gingiva in upper jaw was referred. The right side of maxillary was anesthetized and depigmentation was done by Erbium, Chromium doped Yttrium Scandium Gallium Garnet (Er-Cr: YSGG) laser. Due to scores obtained from Diagnodent which indicated caries in dentin, the cavities were prepared by Er-Cr:YSGG laser. The cavities were restored by composite resin. The patient was advised to keep oral hygiene instructions and use mouthwash. Results: The patient reported no pain after surgery and did not use any systemic antibiotic. After 4 weeks, complete healing was observed. Conclusion: Considering acceptable clinical outcome, Er-Cr: YSGG laser can be considered as an effective method for combination of soft and hard tissue treatment.